RELATIONSHIP OF STUDENTS 'READING INTEREST AND LEARNING READINESS WITH IPS LEARNING OUTCOMES - Annisafitri, Intania i Zahra; Sumilah, Sumilah (Universitas Negeri Semarang, 2019)
The background of this study is the ranking of Indonesian education in the world in 2019 showed that the quality of learning in Indonesia is on 108th ranks. While in the ASEAN region, education in Indonesia takes fifth ranks out of nine countries. The data showed the low quality of education in Indonesia. One of the evidence is the problem occurred on the fourth grade students in elementary school Cluster Diponegoro Semarang. The result of student learning of social studies on fourth grade are still relatively low. This study aims to examine the correlation between: 1) reading interest and social studies learning outcomes; 2) readiness to study and social studies learning outcomes; 3) reading interest, simultaneous learning readiness, and the learning outcomes of social studies. This study used a correlation research design with a quantitative approach. The research samples of 103 students were taken using nonprobability sampling technique by random sampling. The data collection used questionnaire, interview, and documentation. The instrument trials were carried out by validity and reliability tests. The data analysis techniques used the prerequisite test for data analysis, descriptive statistical analysis, correlation analysis and regression analysis. The results showed that: 1) there was a positive correlation between reading interest and social studies learning outcomes the proved by its correlation showed a strong contribution of 48%; 2) there was a positive correlation between learning readiness and social studies learning outcomes the proved by its correlation showed a strong contribution of 49.6%; 3) there was a positive correlation between reading interest and learning readiness simultaneously with social studies learning outcomes the proved by its correlation showed a strong contribution of 58.9%. It can be concluded that there was a positive correlation between reading interest, learning readiness, and social studies learning outcomes of fourth grade students in elementary school Cluster Diponegoro Semarang.